2004
DOI: 10.1007/s00221-004-2074-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of finger force direction in the flexion-extension plane

Abstract: We have examined the interaction among individual finger forces in tasks that required the production of the total force by a subset of fingers in a particular direction in the flexion-extension plane. Nine subjects produced fingertip forces in a prescribed direction with a maximum voluntary contraction (MVC) effort and held the peak force for two seconds. Six finger combinations were tested, four single-finger tasks-Index (I), Middle (M), Ring (R) and Little (L)-one two-digit task (IM), and one four-digit tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Examples include the coordination of articulators during speech (Abbs and Gracco 1984), of arms during loading and unloading (Dufosse et al 1985;Paulingnan et al 1989), of joints during pointing, reaching, standing-up, and swaying (Domkin et al 2002;Freitas et al 2006;Scholz and Schöner 1999;Wang and Stelmach 1998), of muscles during standing and stepping (Krishnamoorthy et al 2003;Wang et al 2005), and of digits during pressing, grasping, and holding an object (Gao et al 2005;Santello and Soechting 2000;Scholz and Latash 1998;Shim et al 2005). Very few studies, however, have addressed synergies at different levels of an involved control hierarchy.…”
Section: Hierarchies Of Synergies In Natural Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include the coordination of articulators during speech (Abbs and Gracco 1984), of arms during loading and unloading (Dufosse et al 1985;Paulingnan et al 1989), of joints during pointing, reaching, standing-up, and swaying (Domkin et al 2002;Freitas et al 2006;Scholz and Schöner 1999;Wang and Stelmach 1998), of muscles during standing and stepping (Krishnamoorthy et al 2003;Wang et al 2005), and of digits during pressing, grasping, and holding an object (Gao et al 2005;Santello and Soechting 2000;Scholz and Latash 1998;Shim et al 2005). Very few studies, however, have addressed synergies at different levels of an involved control hierarchy.…”
Section: Hierarchies Of Synergies In Natural Movementsmentioning
confidence: 99%
“…Very few studies, however, have addressed synergies at different levels of an involved control hierarchy. Those include the studies of digit coordination during prehension (Baud-Bovy and Soechting 2001;Gao et al 2005;Shim et al 2005;Zatsiorsky et al 2003) and of two-arm interaction during pointing (Domkin et al 2002).…”
Section: Hierarchies Of Synergies In Natural Movementsmentioning
confidence: 99%
“…Humans usually exert a larger normal force on an object than absolutely necessary to prevent the object from slipping (Gordon et al 1993, Johansson and Cole 1994, Hager-Ross et al 1996, Gao et al 2005a). The present study also found significantly larger individual digit normal forces than the normal forces that are required mechanically.…”
Section: Internal Force and Safety Marginmentioning
confidence: 99%
“…Studies on the effects of the force direction on the force variability in multilink tasks (which is a topic of the present study) have been mainly limited to fingertip force production in the flexion–extension plane. It was observed that during the fingertip force production the target direction significantly affected the variable error of the force direction, but not the constant error (Gao et al 2005). Fingertip force direction variability was shown to be larger for the force exerted downward and towards the body as compared to other directions (Kapur et al 2010).…”
Section: Introductionmentioning
confidence: 99%